Pengembangan Ekonomi Berbasis Komunitas di Kelurahan Bugih Melalui Program Pengabdian Masyarakat - Ria Kasanova; Syaiful Anam; Hasbullah Hasbullah; Achmad Taufik; Abdul Bari; Mohammad Rudiyanto (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This community development programme (PKM) aims to improve the economic welfare of the community through participatory and empowerment approaches. Bugih Village, located in Pamekasan Sub-district, Pamekasan Regency, has the potential of natural resources that have not been optimally utilised and faces economic problems such as unemployment and low income. The programme began with the identification of local problems and potential, followed by activity planning and targeting of participants. The methods used include training in entrepreneurial skills, mentoring micro-enterprises, and providing access to capital, with active involvement of the community in each stage. The results of the programme show a significant impact on the community's economy, including an increase in income and a decrease in the unemployment rate. Residents who previously relied on informal employment are now able to run more productive micro-enterprises. The training and mentoring provided improved the technical skills and business knowledge of the community, enabling them to manage their businesses more effectively and compete in the market. The assisted micro-enterprises experienced increased production and sales, and gained better access to capital and technology. Analyses show the effectiveness of the participatory approach and empowerment strategies, despite barriers such as limited access to capital and resistance to change from some communities. Enabling factors for success include local government support and active participation of residents. The implications of the programme include strengthened social solidarity and improved local economic capacity, with the expectation that continued support from various parties will ensure the sustainability of the programme and a positive long-term impact on the well-being and economic independence of the community in Kelurahan Bugih.